Abuse and addictive potential of pregabalin - Ratković Dragana; Knežević Vladimir; Dickov Aleksandra; Čomić Maša; Savić Predrag (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction. In the Republic of Serbia, pregabalin was marketed for the first time in 2006. Although the abuse of pregabalin has not been a common topic in the literature so far, it is often seen in everyday practice. Also, it seems that it is more common among addicts. Case outline. We report on a 41-year-old male patient who has a long history of multiple substance abuse and is currently undergoing buprenorphine substitution therapy. He began using pregabalin because it caused euphoria and elevated mood, in daily doses which varies between 1050–2100 mg. The highest daily dose was 4200 mg. At the time he was admitted to the hospital for pregabalin detoxification, he met the general criteria for addiction syndrome. On admission, the patient was tense, anxious, irritable, drenched in sweat, and had insomnia. With an adequate dose of buprenorphine, the patient continued to complain about the reduction of the pregabalin dose and insisted on adjusting the dose. Shortly, he was discharged from hospital at his personal request. After a month, during the check-up examination, he was diagnosed with a relapse of pregabalin use. He was readmitted to the hospital for detoxification treatment, the pregabalin dose was gradually reduced by 100 mg per week. After that the patient went to therapeutic community to continue treatment. Conclusion. This case indicates that practitioners have to be cautious when prescribing pregabalin to people prone to addiction. Further research is needed to identify risk factors for the development of pregabalin abuse syndrome, as well as to create clear guidelines for the treatment of abstinence syndrome.